Effect of Platelet-Rich Plasma on CCl4-Induced Chronic Liver Injury in Male Rats. (23rd February 2014) - Hesami, Zahra; Jamshidzadeh, Akram; Ayatollahi, Maryam; Geramizadeh, Bita; Farshad, Omid; Vahdati, Akbar
Abstract : Platelet-rich plasma (PRP) has been of great concern to the scientists and doctors who are involved in wound healing and regenerative medicine which focuses on repairing and replacing damaged cells and tissues. Growth factors of platelet-rich plasma are cost-effective, available, and is more stable than recombinant human growth factors. Given these valuable properties, we decided to assess the effect of PRP onCCl 4 -induced hepatotoxicity on rats. The rats receivedCCl 4 (1 mL/kg, i.p. 1 : 1 in olive oil) twice per week for 8 weeks. Five weeks afterCCl 4 injection, the rats also received PRP (0.5 mL/kg, s.c.) two days a week for three weeks. Twenty-four hours after lastCCl 4 injection, the animals bled and their livers dissected for biochemical and histopathological studies. Blood analysis was performed to evaluate enzyme activity. The results showed that PRP itself was not toxic for liver and could protect the liver fromCCl 4 -induced histological damages and attenuated oxidative stress by increase in glutathione content and decrease in lipid peroxidative marker of liver tissue. The results of the present study lend support to our beliefs in hepatoprotective effects of PRP.